Change in Collaboration over Time: A Specific Case in a Student Work Placement Scenario - Bird, Alice (Proceedings of the International Conference on Networked Learning, 2006)
The current study investigates how collaboration, mediated by technology, changed as a new community of practice developed. In this case, the community involved work placement students, recruited to support academic staff development in the virtual learning environments at Liverpool John Moores University. The study is based on an analysis of placement student participation in an asynchronous discussion board, responses to an online questionnaire and further information derived from interviews conducted with four of the participants. Some key factors influencing change in collaboration are identified with suggestions made for future research in this area.